Autoantibodies to Thrombomodulin: Development of an Enzyme Immunoassay and a Survey of their Frequency in Patients with the Lupus Anticoagulant - Gibson, John; Nelson, Margaret; Brown, Ross; Salem, Hatem; Kronenberg, Harry (Thrombosis and Haemostasis, 1992)
In order to investigate the possibility that autoantibodies to thrombomodulin (TM) may exist in patients with the lupus anticoagulant (LA) and perhaps be implicated in the pathogenesis of recurrent thrombosis seen in such patients, we developed an enzyme-immunoassay to screen serum samples for anti-human TM activity. The major technical problem encountered in developing this assay was to reduce the non-specific binding of serum components from both the LA positive and the negative population. Considerable reduction of non-specific binding was achieved by use of a phosphate/citrate buffer at pH 8.0 and the use of an optimal sample dilution of 1/40. In addition, samples were always tested in parallel in blank wells and results are expressed as an OD ratio. Samples from 113 patients with the LA were assayed and compared to 78 patients referred for LA testing but found to be negative. The mean OD values for the LA positive patients (± SD) was 1.36 (0.44) with a range of 0.78-2.57. This was virtually identical to the values for the LA negative population (1.38 ± 0.40, range 0.76-2.77). The results of this study indicate that there is no evidence for the presence of a significant autoantibody activity to TM in patients with the LA when compared to LA negative patients. If such autoantibodies do exist their frequency must be quite low.